THE IMPACT OF NUTRITIONAL STATUS ON GROWTH AND ANTHROPOMETRIC PARAMETERS IN CHILDREN - Trpkovska, Biljana; Zafirova, Biljana; Matveeva, Niki; Cadikovska, Elizabeta; Bojadzieva, Biljana; Kordoska, Jovana; Klisarovska, Violeta; Hristova, Emilija; Dimceva, Anita Hristova; Krstev, Toni (Journal of Morphological Sciences, 2024)
Evaluation of sex-specific differences of anthropometric parameters as impact of growth and nutritional status in preschool children from Macedonian nationality. The study included a total of 200 healthy 5-5.99 years-old preschool children from Macedonian nationality. Twelve anthropometric parameters were measured, defining longitudinal, circular and transversal dimensionality of the skeleton using standard technique and instruments for measurement. The following indices were selected and calculated: weight-for –age; height-for-age and BMI. Skin –folds (triceps, scapula and thigh) were also measured. Sex-specific differences for almost all anthropometric parameters were detected, but they were not significant. Boys showed higher values than girls regarding height, weight but for BMI were not significant. Values at the 50 th percentile in boys were 20 kg for BW, 113.2 cm for BH and 15.94 kg/m². The values of these parameters in girls were 20 kg for BW, 115.4 cm for BH and 15.64 for kg/m² for BMI. The values for skin fold for biceps were higher in boys (10.6. ± 3.9)  instead of girls (9.7 ± 3.3). The results obtained can be used for criteria for assessment and detecting deviations in growth and nutritional status in preschool children. Key words: anthropometry, growth, nutritional status, preschool children.